FENOMENA STUNTING SEBAGAI DAMPAK DEGRADASI KESEJAHTERAAN SOSIAL-EKONOMI MASYARAKAT - Jelahut, Yosef Emanuel; Jehamat, Lasarus; Oiladang, Chris S.; Jelahut, Felisianus Efrem (Jurnal Dakwah Tabligh, 2023)
The purpose of this study was to find out how the Sociological Study of Health on Stunting Phenomena in South Amarasi District, Kupang Regency. The urgency of this research is that the people of Nekmese Village, Amarasi Selatan District, Kupang Regency need information about their conceptions and meanings related to stunting so that from here they can realize that there is one of the root causes of stunting. The theory used in this research is Social Action Theory. This research method is qualitative with a case study approach. The results of this study show that Nekmese village is one of the villages with the highest prevalence of stunting, namely 34.0% among the five villages in the South Amarasi sub-district. With the high stunting rate in this village, the researchers assume that many other factors are quite complex apart from the health factor itself, for example, the economy, education, and social aspects. In Nekmese village, the causes of malnutrition are very diverse, both direct and indirect. The causes of malnutrition can differ between families and between the social environment of each member of society. In the village of Nekmese Kec. South Amarasi the problem of high stunting rates is also caused by parenting or parenting by parents or caregivers.